A call to excellence in patient experience - Geoffrey Silvera (The Beryl Institute, 2016)
In this address, the incoming associate editor describes his early experience with the Patient Experience Journal (PXJ) and issues a call to action to the PXJ community. In the call to action, the PXJ community is asked to build upon our collective history of scholastic and practical excellence. The combination of practical relevance and methodological rigor in our contributions will help to ensure a future in which patient experience is paramount in health service delivery conversations. In addition, gaps in the patient experience literature and emergent opportunities for theoretical and practical contributions are recommended.